Des monuments aux morts entre laïcité et ferveur religieuse : un patrimoine hors-la-loi ? - Claude Dupuis (In Situ)
After the French law of December 1905 separating the Church and the State, monuments erected in the public realm were supposed to be entirely devoid of religious symbolism and war memorials were not exempted from this rule. Yet many sponsors and artists managed to get round this ban. In particular by using the female figure, sculptors often succeeded in introducing a religious element into their creation. This article takes a look at a selection of war memorials scattered throughout France in order to see how references to themes of a religious nature were used, either respecting the principle of secularism or subverting it.